Transdisciplinary digital change: science and architecture - Correia, Ricardo Mendes; Paio, A.; Brandão, Filipe J.S. (4th International Symposium Formal Methods in Architecture, 2018)
The article is part of an ongoing research whose aim is to outline a historical perspective of transdisciplinary digital architecture through the work of key personalities by the establishment of links between them. Researches on digital architecture history are generally grounded on methods with limited sets of primary sources and data is lost. The research methodology will be also grounded the availability of digital data sources in the internet, not created and structured with research purposes but with the use of data-driven and geospatial approaches can give researchers a way to address multidimensional aspects and facts. This article presents the preliminary results of a research the related to a paradigm shift in the teaching of architectural design.